Biocontrol of Moler Diseases (Fusarium oxysporum f. sp capae (Snyder and Hans)) on Shallot with Endophytic Bacteria - Resti , Zurai; Darnetty, Darnetty; Khairul , Ujang; Reflin , Reflin; Siregar , Sri Lestari Kurnia; Tores, Farah Nabila (Green Engineering Society, 2024)
Fusarium Basal Root (FBR) disease locally known as